The Multi-Party Interim Appeal Arbitration Arrangement (MPIA): A Legal Analysis of Its Disadvantages and Implications for WTO Reform (International Journal of Scientific Research and Management (IJSRM), 2025)
The Multi-Party Interim Appeal Arbitration Arrangement (MPIA) was introduced as a temporary solution to the paralysis of the World Trade Organization (WTO) Appellate Body. This paper examines the MPIA’s structure, legal framework, and effectiveness within the WTO dispute settlement system. It highlights the MPIA’s voluntary nature, limited participation, and procedural innovations while assessing its impact on international trade governance. Despite maintaining a two-stage dispute resolution process, the MPIA faces critical challenges, including its non-binding status, the exclusion of major economies such as the United States, and concerns over enforceability. Additionally, its provisions lack legal precedent-setting power, limiting its broader applicability within WTO jurisprudence. The paper argues that while the MPIA offers a temporary alternative, it cannot fully replace the WTO’s Dispute Settlement Mechanism (DSM). Instead, it underscores the need for a comprehensive reform of the WTO dispute resolution system to ensure inclusivity, enforceability, and long-term stability. The paper concludes that the MPIA represents both an interim measure and a potential pathway toward future WTO dispute settlement reform, but its long-term viability depends on broader institutional and political developments within global trade governance.